DNA replication-mediated recombination of molecules of adenovirus 2 DNA. - Wolgemuth, D J (1981)
Molecules of adenovirus 2 DNA were isolated as nucleoprotein complexes late in infection of HeLa cells and examined by electron microscopy. Some were interpreted as representing intermediates in recombination events. The structures observed were consistent with predicted intermediates according to the model for genetic recombination proposed by Meselson and Radding [Meselson, M. S. & Radding, C. M. (1975) Proc. Natl. Acad. Sci. USA 72, 358-361] and constitute physical evidence from animal cells in support of this model.